Resistencia a enfermedades virales - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
The main activities of bean virology at CIAT in 1984 involved screening for BCMV dominant resistance (selection of homozygous BCMV resistant lines), BCMV multiple gene resistance, BCMV recessive gene immunity, and the management and prognosis of other important viral diseases of beans involving the incorporation of multiple resistance (BCMV and BYMV) into all the germplasm improved collaboratively. Main research efforts of BCMV multiple gene resistance concentrated on the scarcity of black root resistance sources, the relatively limited knowledge available on the possible combination of dominant and recessive genes, the frequency of black root resistant genotypes, and the response of plants possessing different combinations of dominant and recessive genes. Likewise, 14,823 CIAT accessions were evaluated for the presence of useful recessive, or dominant combined with recessive, genes that are resistant to BCMV and black root. Studies were also conducted to assess the effects of BSMV on the main production components of var. Diacol Calima. (CIAT)